Sustainability assessment of water hyacinth with swine dung for biogas production, methane enhancement, and biofertilizer - Yuwalee Unpaprom (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Anaerobic digestion (AD) processes performed biogas production of crushed water hyacinth (WH) combined with swine dung (SD) was investigated in this study. AD carried out for 45 days at mesophilic temperatures ranging from 34 to 36 °C. Alkali (sodium hydroxide, NaOH) hydrolysis of WH was performed prior to batch dry AD at four different mild concentrations. Results revealed that NaOH pretreated samples produced a high yield of biogas than untreated (raw) samples. The scanning electron microscopy (SEM) was thus used to provide supporting confirmation on the main structural transformations that chanced in WH. The optimum WH concentration in the 1:1 ratio of co-digestion mixture with SD produced the highest methane yield, and the biogas composition of carbon dioxide, CO2 (29.08%), methane, CH4 (68.89%), and 1.09% of hydrogen sulfide, H2S. Upgraded biogas through chemical purification results revealed that CH4 and CO2 were 92.35% and 8.04%, respectively. Enhanced biogas high heating value was 36.83 MJ/m3 and low heating value 33.18 MJ/m3. Furthermore, the digestate has high nutrient concentrations that can potentially use as fertilizer; it contains nutrients nitrogen, phosphorus, potassium were 107.506, 18.838 and 39.552 g kg−1, respectively. The digestate from biogas fermenter was confirmed to be an efficient alternative fertilizer with high nutrients and environmentally-friendly comparing to chemical fertilizer.